Visuo-Haptic Interactions in Unilateral Spatial Neglect: The Cross Modal Judd Illusion - Mancini, Flavia; Bricolo, Emanuela; Mattioli, Flavia C.; Vallar, Giuseppe (Frontiers in Psychology, 2011)
Unilateral spatial neglect (USN) has been mainly investigated in the visual modality; only few studies compared spatial neglect across different sensory modalities, and explored their multisensory interactions, with controversial results. We investigated the integration between vision and haptics, through a bisection task of a cross modal illusion, the Judd variant of the Müller-Lyer illusion. We examined right-brain-damaged patients with (n = 7) and without (n = 7) left USN, and neurologically unimpaired participants (n = 14) in the bisection of Judd stimuli under visual, haptic, and visuo-haptic presentation. Neglect patients showed the characteristic rightward bias in the bisection of the baseline stimuli in the visual modality, but not in the haptic and visuo-haptic conditions. The illusory effects were preserved in each group and in each modality, indicating that the processing of the cross modal illusion is independent of the presence of deficits of spatial attention and representation. Spatial neglect can be modality-specific, but visual and tactile sensory inputs are properly integrated.